Cluster headache without autonomic symptoms: why is it different? - Martins, I (2005)
BACKGROUND: Some patients with otherwise typical cluster headache (CH) have persistent attacks free of cranial autonomic symptoms (CAS). The factors responsible for this atypical presentation are not known. OBJECTIVES: To identify factors associated to the absence of CAS in patients with CH. METHODS: A prospective series of 157 patients with the diagnosis of CH was analyzed, comparing 148 typical CH patients with 9 CH patients without CAS. RESULTS: Patients without CAS reported significantly less intense attacks (P = .003) when compared to those with CAS. There was also a tendency (not reaching statistical significance) for a higher frequency of females and chronic CH among those without CAS. Otherwise, there were no differences between the two groups (in age, duration of illness, follow-up time, attack duration or frequency, nor side or site of pain). A logistic regression analysis showed that only pain intensity could explain the difference between the two groups, since the other explanatory variables were also associated with different intensity of attacks. CONCLUSIONS: These results support the hypothesis that CH without cranial autonomic symptoms represents a milder form of CH.